A randomized, double-blind, placebo-controlled phase 2 pilot trial evaluating a novel, vaginal softgel capsule containing solubilized estradiol. Issue 5 (May 2016) - Pickar, James H.; Amadio, Julia M.; Hill, John M.; Bernick, Brian A.; Mirkin, Sebastian
Abstract: Objective: The aim of the study was to evaluate the safety and efficacy of vaginal estradiol (E2 ) softgel capsules for moderate-to-severe symptoms of vulvar and vaginal atrophy (VVA). Previous phase 1 studies showed lower systemic estrogen concentrations with this softgel capsule compared with an approved low-dose vaginal E2 tablet. Methods: In this randomized, double-blind, placebo-controlled phase 2 study, 50 postmenopausal women (aged 40-75 y) with at least1 moderate-to-severe VVA symptom received 10 μg vaginal E2 softgel capsules or placebo daily for 14 days. Changes from baseline in vaginal maturation index, investigator's assessment of vaginal mucosa (secretions, epithelial integrity, epithelial surface thickness, color), vaginal pH, and most bothersome symptom were assessed. Adverse events were evaluated. Results: Compared with placebo, the percentage of superficial (35.2 percentage points [pp] vs 8.75 pp; P  = 0.0002) and intermediate (18.7 pp vs −3.54 pp; P  = 0.0017) cells increased from baseline significantly more with vaginal E2 capsules, and parabasal cells decreased significantly more (−54.4 pp vs −4.80 pp; P  < 0.0001). Vaginal pH decreased significantly more with vaginal E2 capsules (−0.974 vs −0.339; P  = 0.0002). Decreases in severity of atrophic effects on vaginal epithelial integrity (−0.342 vs 0.176; P  = 0.0001) and secretions (−0.643 vs −0.274; P  = 0.0401) were significantly greater with vaginal E2 capsules vs placebo. There was no statistical difference in most bothersome symptom severity change from baseline. No serious adverse events were reported. Conclusions: Vaginal E2 softgel capsules are a safe, effective, local treatment option for postmenopausal women with moderate-to-severe VVA, with lower systemic estrogen absorption than currently available intravaginal treatments.